2015
DOI: 10.1002/jcc.24055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and acceleration of binding energy calculations for protein–ligand complexes by the fragment molecular orbital method

Abstract: In the field of drug discovery, it is important to accurately predict the binding affinities between target proteins and drug applicant molecules. Many of the computational methods available for evaluating binding affinities have adopted molecular mechanics-based force fields, although they cannot fully describe protein-ligand interactions. A noteworthy computational method in development involves large-scale electronic structure calculations. Fragment molecular orbital (FMO) method, which is one of such large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…In it, fragments are divided into layers, and each layer is allowed to have its own basis set and method. In a typical example, a protein–ligand binding site is described with a higher level than the rest of the protein . Although the formulation is general for multiple layers, so far at most two layers have been used.…”
Section: Physical Model Of Fmomentioning
confidence: 99%
“…In it, fragments are divided into layers, and each layer is allowed to have its own basis set and method. In a typical example, a protein–ligand binding site is described with a higher level than the rest of the protein . Although the formulation is general for multiple layers, so far at most two layers have been used.…”
Section: Physical Model Of Fmomentioning
confidence: 99%
“…Some previous studies combining FMO calculations and regression analysis have been reported, including a Linear Expression by Representative Energy Terms (LERE)-QSAR analysis by Chuman and colleagues, 8) a PLS regression of CDK2 inhibitors by Mazanetz et al 9) and a PLS regression of FK506-binding protein (FKBP) ligands by Otsuka et al 10) In all cases, the usefulness of the FMO method and regression analysis was demonstrated. However, in these studies, the interaction/binding energy between the whole protein and a single ligand was used as a descriptor, and individual energy information about the amino acid residue fragments was not used.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach neglects, among other entropic contributions, the influence of solvation effects. To include the latter, one would need a much more time-consuming method, for instance free-energy perturbation (FEP), Molecular Mechanics/Poisson-Boltzmann, Molecular Mechanics/Generalized Born Surface Area (MM/GBSA and MM/PBSA, respectively) [ 36 ] or Fragment Molecular Orbital (FMO) approach [ 37 ]. The quantum chemical methods (like DFT or MP2) are rather not combined with empirical solvation or ligand entropy estimates [ 36 ], and therefore they should work only if the neglected contributions to the energy of binding are similar within the studied set of complexes.…”
Section: Introductionmentioning
confidence: 99%